From classroom to work room: How grammar yields clarity of message and confidence in the professional world through simulated learning from academic halls - Jason V. Chavez; Erwyn O. Valencia; Mary Ruth D. Diamante; Etchel B. Palma; Dr. Elena B. Panugot; Pearly Jade E. Samilo; Neña Vanessa A. Cabiles; Darrel M. Ocampo; Arniza J. Kiram; Pearl Kathlene D. Francisco (Environment and Social Psychology, 2025)
Despite the crucial role of grammar in professional communication, limited research has examined how simulated learning experiences in academic settings foster grammatical competence that translates into workplace clarity and confidence. This exploratory study addresses this gap by investigating how simulated classroom activities such as role-plays, presentations, and mock interviews help students apply grammar effectively to enhance message clarity and build communication confidence as they transition into the professional world. Using purposive sampling, the study engages 18 recent graduates currently employed in various industries. Data were collected through one-on-one interviews and analyzed using reflexive thematic analysis to capture in-depth perspectives on participants’ classroom experiences and their relevance to professional communication. Preliminary expectations suggest that grammar-focused simulated learning strengthens students’ ability to structure and articulate ideas clearly, while also boosting their self-assurance in professional settings. The findings aim to provide insights for educators seeking to align grammar instruction with real-world communication demands, ultimately bridging the gap between academic preparation and workplace readiness.